Optimizing Telework with Exercise: An Exploration of the Curvilinear Relationship between Telework Intensity and Work Engagement - Huo, Weiwei; Liang, Bingqian; Liang, Yongmei; Song, Mengli; Wang, Yixin (Behavioral sciences, 2024)
The sudden COVID-19 crisis disrupted people’s pace of life. Meanwhile, telework has gradually attracted public attention and become a regular mechanism for organizations. In this context, self-regulation theory was utilized to explore the impact of telework intensity on work engagement. Data were collected from 304 employees across three time points, and the results supported a curvilinear relationship between telework intensity and work engagement. Specifically, it was discovered that employees exhibited the highest levels of work engagement at moderate levels of telework intensity. Additionally, based on the strength model of self-control, the research identified self-control as playing a mediating role between telework intensity and work engagement. Finally, the study revealed that the duration of physical exercise moderated the relationship between telework intensity and self-control. Long-term physical exercise was found to prolong and enhance the positive effects of telework intensity on self-control, thereby boosting employee work engagement. This study provided unique and valuable insights into maintaining employee engagement in telework.